Alcohol use disorder and its association with quality of life and mortality in Chinese male adults: a population-based cohort study - Jiapeng Lu; Yang Yang; Jianlan Cui; Wei Xu; Chaoqun Wu; Jing Li; Xi Li (BMC Public Health, 2022)
Abstract Aims We aimed to demonstrate the distribution of alcohol use disorder (AUD) in China and assess its association with quality of life and mortality. Methods We studied 367 120 men aged 35–75 years from 31 provinces in the China Patient-Centered Evaluative Assessment of Cardiac Events (PEACE) Million Persons Project. At baseline, AUD was assessed by alcohol use disorders identification test score, and EQ-5D-3L questionnaire was used to measure the quality of life. Mortality data was collected via National Mortality Surveillance System and Vital Registration. Mixed models were fitted to assess the associations of AUD with quality of life, and Cox proportional hazard models were fitted for the associations with all-cause and cause-specific mortality. Results We identified 39 163 men with AUD, which accounted for 10.7% of male participants and 25.8% of male drinkers. In the multivariable analysis, male drinkers who were aged 45–54 years, with higher education level, currently smoking, obese, with diagnosed hypertension, and without diagnosed cardiovascular diseases had higher rates of AUD. Male drinkers with AUD were less likely to have optimal QOL compared with those without AUD (OR: 0.63, 95% CI: 0.61–0.65, P < 0.001). Moreover, among male drinkers, AUD was prospectively associated with a 20% higher risk for all-cause mortality and a 30% higher risk for mortality from cancer. Conclusions In China one fourth of men who drank alcohol had AUD, which was associated with lower QOL and higher risk of all-cause mortality. National policies or strategies are urgently needed to control alcohol-related harms.